In vitro evaluation of microbial adhesion on the different surface roughness of acrylic resin specific for ocular prosthesis - Andreotti, Agda Marobo [UNESP]; De Sousa, Cecília Alves [UNESP]; Goiato, Marcelo Coelho [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; Duque, Cristiane [UNESP]; Moreno, Amália; Dos Santos, Daniela Micheline [UNESP] (Thieme, 2018)
Objective: The purpose of this study was to evaluate the influence of surface roughness in biofilm formation of four microorganisms (Staphylococcus epidermidis, Staphylococcus aureus, Enterococcus faecalis, and Candida albicans) on acrylic resin surface of ocular prostheses. Materials and Methods: Acrylic resin samples were divided into six groups according to polishing: Group 1200S (1200 grit + silica solution); Group 1200; Group 800; Group 400; Group 120 and Group unpolished. Surface roughness was measured using a profilometer and surface images obtained with atomic force microscopy. Microbial growth was evaluated after 4, 24, and 48 hours of incubation by counting colony-forming units. Statistical Analysis Used: For roughness, it was performed 1-way ANOVA and parametric Tukey test α5% (P ≤ 0.05). For CFU data found, it was applied Kruskal-Wallis and Mann-Whitney tests. Results: Group 120 and 400 presented the highest roughness values. For S. epidermidis and S. aureus, Group 1200S presented the lowest values of microbial growth. For E. faecalis at 4 hour, microbial growth was not observed. C. albicans did not adhere to the acrylic resin. Except for Group 1200S, different surface roughnesses did not statistically interfere with microbial adhesion and growth on acrylic surfaces of ocular prostheses. Conclusions: The roughness did not interfere with the microbial adhesion of the microorganisms evaluated. The use of silica decreases significantly microbial growth.
Keywords: Acrylic resin; Biofilm; Microbial adhesion; Ocular prosthesis